1994
DOI: 10.1111/j.1399-302x.1994.tb00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of immunoglobulin G by periodontal bacteria

Abstract: Several subgingival microorganisms were tested for their ability to utilize human immunoglobulin G (IgG) as a substrate for growth. This was done using a protein-free chemically defined medium, supplemented with IgG. Stimulation of growth was observed for Capnocytophaga ochracea, Porphyromonas asaccharolytica, Porphyromonas endodontalis, Porphyromonas gingivalis, Prevotella intermedia, Prevotella oralis, Lactobacillus catenaforme and Streptococcus intermedius. Immunoelectrophoresis, sodium dodecyl sulfate-poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1995
1995
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…In a previous study, we demonstrated the ability of Porphyromonas and Prevotella species to use IgG as the sole source of amino acids while growing in a chemically defined medium (11). Here, using a relatively rich medium, we detected growth enhancement of P. intermedia and P. nigrescens by up to 130%.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In a previous study, we demonstrated the ability of Porphyromonas and Prevotella species to use IgG as the sole source of amino acids while growing in a chemically defined medium (11). Here, using a relatively rich medium, we detected growth enhancement of P. intermedia and P. nigrescens by up to 130%.…”
Section: Discussionmentioning
confidence: 50%
“…Although P. intermedia may be less virulent than Porphyromonas gingivalis (30), it produces an array of virulence factors (21), of which the capacity to degrade immunoglobulins is thought to be important. Bacteria with this ability can provide themselves (8,11) and other bacteria (27) with nutrients while simultaneously impeding host defense (3,6). Several laboratories have isolated and characterized P. gingivalis proteases (4,7,20,29), but less attention has been paid to those of P. intermedia.…”
mentioning
confidence: 99%
“…A number of periodontal bacteria are known to exploit host sialylated glycoproteins as a nutrient source. For example, immunoglobulin G, which is abundant in gingival crevicular fluid, can support the growth of P. gingivalis, Prevotella oralis, and a number of other periodontal pathogens (20). The NanH of B. fragilis is important for growth in vivo: sialidase-deficient mutants of B. fragilis have impaired growth in a rat pouch model (14).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry is an established technique for protein detection, but staining for immunoglobulin may be unreliable due to the high background staining caused by non-specific binding to other immunoglobulins within the tissues [15] and with serumderived immunoglobulins which bathe the tissues [6]. In addition, the detection of immunoglobulin proteins in vivo presents several technical difficulties because of degradation by neutrophil elastase [16] and oxidants [17] in inflamed sites as well as by immunoglobulin-degrading proteases from periodontal bacteria [18,19]. Our attempts to localize immunoglobulin in gingival tissues using MoAbs have been disappointing due to the excessive background staining thought to be due to the systemic and local soluble immunoglobulin presence.…”
Section: Introductionmentioning
confidence: 99%